Перспективы использования систем поддержки принятия решений в задачах рационального природопользования - Волков, А.И. (Культура народов Причерноморья, 2013)
Системы поддержки принятия решений, в настоящее время, получили широкое распространение в различных сферах деятельности, в том числе в области рационального природопользования. В рамках данного исследования разработана система поддержки принятия решений, функционал которой обеспечивает анализ территорий на предмет выделения оптимального вида осуществляемой в ее пределах хозяйственной деятельности. Также предложен алгоритм комплексной бальной оценки территорий. Системи підтримки прийняття рішень, в теперішній час, набули широке поширення у різних сферах діяльності, зокрема у сфері раціонального природокористування. У наведеному дослідженні розроблена система підтримки прийняття рішень, функціонал якої забезпечує аналіз територій на предмет виділення оптимального виду господарської діяльності, що повинна здійснюватися у її границях. Також запропонований алгоритм комплексної бальної оцінки територій. Decision support systems (DSS) is a computer-based information system that supports organizational decision-making activities. Nowadays, concept of DSS is widespread in different research fields also in environmental management sector. Advantage of any DSS is a flexible interface which provides convenient tools for processing, analysis and visualization of information. An important feature of environmental DSS is ability to differentiate and rank areas for strategic planning and future development of the region. The main goal of the environmental DSS is identification of optimal treatment for area in question. Since all indexes and figures which describe environmental conditions have different scale and measure units it was designed comprehensive approach for point scoring system. Approbation of designed environmental DSS was accomplished for areas surrounded liman Tiligulskiy (Odessa region, Ukraine). The research concerns assessment of liman Tiligulskiy recreational potential and possibilities of using it for recreation. Liman Tiligulskiy was chosen as soon as it is situated far from big cities and it’s recourses are relatively unexploited. The environmental assessment of liman’s area is based on beaches quality, climatic conditions, mud mineral resources, abrasion and landslides characteristics and technigenic load levels. The research results show three options of liman’s land use: (a1) restriction of any economic activities; (a2) expanding recreational sector; (a3) use of areas for agricultural purposes. The research results can be used as a basis for the further development of tourism sector and management of recreational sources of the area in question.